Oxidizes Low Density Lipoprotein Cytoxicity and Vascular Diseases - Gieseg, Steven P.; Zunika, Amit; Crone, Elizabeth (EUniversity of Toronto, Department of Nutritional Sciences, Faculty of Medicine, Toronto, 2009)
The formation of oxidized low density lipoprotien (oxLDL) within atherosclerotic plaques is a significant event, which appears to drive the transition from fatty streaks to advanced complex plaque cytotoxic agent that triggers a number of competing cell death machanisms.